Young people as competent community builders: a challenge to social work - Finn, Janet L.; Checkoway, Barry (1998)
This article reports on a pilot study of exemplary community-based youth initiatives in the United States in which young people are active participants in solving problems, planning programs, and providing services at the community level. The article presents brief summaries of six initiatives illustrating a range of youth participation in the issues that affect their lives and their communities. These diverse initiatives exemplify a view of young people as resources and promote individual, organizational, and community development. They were selected on the basis of their commitment to youth involvement, capacity building, collaboration, cultural awareness, community-defined concerns, leadership development, continuity, and comprehensive and change-oriented practice. The initiatives provide lessons for practice and challenge social workers to build meaningful partnerships and practice approaches that challenge problem-oriented interventions and recognize young people as competent community builders. - Reproduced
Keywords: Social work - United States; Youth - United States; Youth